Evaluation of the Adjuvant Activity of Propranolol, a Beta-Adrenergic Receptor Antagonist, on Efficacy of a Malaria Vaccine Model in BALB/c Mice - Shahram Shahabi; Habib Mohammadzadeh Hajipirloo; Seyed Ahmad Keramati; Khosrow Hazrati Tappeh; Arezoo Bozorgomid (Iranian Journal of Allergy, Asthma and Immunology, 2014)
We have previously shown the adjuvant activity of propranolol (PRP) (a beta-adrenergic receptor antagonist) using a vaccine model for Salmonella typhimurium. In this study PRP was used as an adjuvant in combination with Plasmodium  berghei  (P. berghei)  whole blood stage (PWBS) antigens. BALB/c mice were immunized three times with a 2-week interval, either PWBS vaccine alone or in combination with the adjuvant alum or propranolol. The control group received phosphate buffered saline. Evaluation of the cellular and humoral immunity was performed by measurement of interferon (IFN)-γ, tumor necrosis factor (TNF)-α, lymphocyte proliferation, total IgG  and IgG2a  in the  control  and  immunized groups. Furthermore, Clinical evaluations were carried out by analyze survival rate and parasitemia of the mice. Our results showed that the mice immunized with propranolol induced higher levels of antibody, IFN-γ and TNF-α as well as stronger lymphocyte proliferative responses compared with other groups. This resulted in improved protective immunity against Plasmodium berghei. Administration of  the  PRP  as an  adjuvant in combination  with the  PWBS Antigen vaccine can shift the immune responses to a T helper1 pattern and enhance the protective immunity.